2002
DOI: 10.1259/bjr.75.895.750590
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose quantities and risk in neonates in a special care baby unit

Abstract: Radiographs are taken in the neonatal period most commonly to assist in the diagnosis and management of respiratory difficulties. Frequent accurate radiographic assessment is required and a knowledge of the radiation dose is necessary to justify such exposures. A survey of radiation doses to neonates from diagnostic radiography (chest and abdomen) has been carried out in the special care baby unit of the Royal Free Hospital. Entrance surface dose (ESD) was calculated from quality control measurements on the X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
3
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 9 publications
(13 reference statements)
2
37
3
10
Order By: Relevance
“…The present study Chapple et al (6) Wraith et al Armpilia et al (19) Brindhaban e Al-Khalifah have shown that the equipment time and voltage accuracy and reproducibility are in compliance with the technical performance standards established by the Brazilian authorities (23) . However, the half-value layer at 80 kV (1.75 mm of Al) was significantly below of the minimum value established by the mentioned technical standard (2.3 mm of Al); that is to say, the x-ray tube output is low, even with the utilization of inadequate filtration.…”
Section: Referencesupporting
confidence: 69%
See 1 more Smart Citation
“…The present study Chapple et al (6) Wraith et al Armpilia et al (19) Brindhaban e Al-Khalifah have shown that the equipment time and voltage accuracy and reproducibility are in compliance with the technical performance standards established by the Brazilian authorities (23) . However, the half-value layer at 80 kV (1.75 mm of Al) was significantly below of the minimum value established by the mentioned technical standard (2.3 mm of Al); that is to say, the x-ray tube output is low, even with the utilization of inadequate filtration.…”
Section: Referencesupporting
confidence: 69%
“…This is a function of the field size, equipment filtration and radiographic technique employed. A fixed value of 1.16 for BSF was adopted in the present study (19) .…”
Section: Methodsmentioning
confidence: 99%
“…The International Commission on Radiological Protection (ICRP) has both encouraged "authorized bodies" to set diagnostic reference levels (DRLs) as dose optimization tools 4 , consistent with regional, national or local area to which they apply and also defined the concept of effective dose (E) 4 , which has become an accepted method for estimating dose and associated risks in diagnostic radiology. Some studies have been interested to dose index, like entrance surface dose (ESD) or dose area products (DAP) measurements [5][6][7][8][9][10] , but only few ones addressed to effective dose (E) comparison, for newborns and especially preterm infants [9][10][11] . However, in Tunisia, the contribution of these examinations to the patient's exposure is still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Special attention should be given to neonatal imaging since doses during childhood results in increased risk of cancers. Therefore it is important to ensure that radiation doses from radiographic examinations are to be kept to the minimum whilst maintaining the quality of radiographic images (Armpilia, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Lower noise level results in better radiographic image because it improves contrast resolution, but normally at the cost of a higher patient dose. (Armpilia, 2002) Our aim is to use the X-ray beam efficiently, producing the best possible image with good resolution and low noise with a dose reasonable to the patient. The balance between patient dose and noise is the most challenging task in optimisation.…”
Section: Introductionmentioning
confidence: 99%